2022
DOI: 10.21037/atm-21-6809
|View full text |Cite
|
Sign up to set email alerts
|

Application of a custom-made single-incision sealing device in laparoscopic surgery for totally extraperitoneal herniorrhaphy: initial experience

Abstract: Background: In this research, the safety and feasibility of single-incision laparoscopic surgery for total intraperitoneal herniorrhaphy (SILS-TEP) was clarified through a customized single-port device.Methods: A 2.5 cm curved incision was made along the lower umbilical margin. The subcutaneous fatty tissue was removed by electrotomy or blunt dissection to form a 5.0 cm preperitoneal space under the posterior sheath. The Iconport single-hole device silicone sealing sleeve was wedged under the posterior rectus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, SIL-TEP has disadvantages that cannot be overcome by improving surgical skills. Since 2018, we have attempted to successfully perform single-incision inguinal hernia repair via the TPP approach[ 7 , 8 ]. In addition, comparison of SIL-TPP and SIL-TEP showed that SIL-TPP could overcome the disadvantages of SIL-TEP, such as a confined operation space and adverse factors resulting from peritoneum rupture[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, SIL-TEP has disadvantages that cannot be overcome by improving surgical skills. Since 2018, we have attempted to successfully perform single-incision inguinal hernia repair via the TPP approach[ 7 , 8 ]. In addition, comparison of SIL-TPP and SIL-TEP showed that SIL-TPP could overcome the disadvantages of SIL-TEP, such as a confined operation space and adverse factors resulting from peritoneum rupture[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…201110229309.4) (Figures 1 and 2 ). The results suggested that SIL-TPP was a safe and feasible procedure[ 7 , 8 ]. In the initial stage of the study, peritoneal damage occurred in 3 patients at the beginning of the operation, and the author immediately converted to conventional TAPP surgery due to a lack of experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…US9,393,003B2) (Figure 1) to perform transumbilical single-port laparoscopic appendectomy, cholecystectomy, hernia repair and enterolysis. 6,7 By alternating between the different operation holes on the operation panel to eliminate interference, the target operation field has omni-directional exposure. The hard material operation panel supports the lens and equipment 8 so that one can expose the operation field from any angle.…”
Section: Technical Solutionmentioning
confidence: 99%